Pemilihan model kerugian dengan ujian statistik dan aplikasi model dalam insurans - Ismail, Noriszura (Universiti Utara Malaysia, 2001)
Selecting loss distribution model by using statistical tests should be done to make sure it is accepted and the model selected can be applied in insurance.This study aims to select the best loss distribution model by applying statistical fitting test on seveal fitted Loss distribution model. The loss distribution model represents sample data from motor insurance claims in Malaysia. The model is obtained by using maximum likelihood estimation. The statistical tests used are Pearson: goodness-of fit statistic and Kolmogorov-Smirnov statistic. Based on results from maximum likelihood estimation and statistical tests, a single best model will be selected and the model will be applied in insurance.